Analysis of Factors Affecting the Quality of E-Learning and Student Learning Outcomes - Sahusilawane, Wildoms; Hiariey, Lilian Sarah (Indonesian Journal of Advanced Research, 2025)
This research examines the factors affecting the quality of e-learning and student learning outcomes at Universitas Terbuka. We sought to investigate the effect of these variables on the quality of e-learning and observe its impact on student learning outcomes. This study adopts a quantitative approach, where questionnaires are distributed through Google Forms and distributed directly to respondents to assess factors affecting the quality of e-learning and student learning outcomes.  The study examined a sample size of 96 students across five regional offices at Universitas Terbuka. The statistical technique used for the analysis is linear regression in SPSS software. The study results indicate that media and material quality positively and significantly impact e-learning quality, while ease of use and information quality show no significant effect. Additionally, ease of use, information quality, material quality and media quality do not significantly affect learning outcomes. However, e-learning quality demonstrates a positive and significant influence on student learning outcomes.